MAXIMUM LIKELIHOOD ESTIMATION FOR THE WEIGHTED LINDLEY DISTRIBUTION PARAMETERS UNDER DIFFERENT TYPES OF CENSORING - RAMOS, Pedro Luiz; LOUZADA, Francisco; CANCHO, Vicente Garibay (Brazilian Journal of Biometrics, 2017)
In this paper the maximum likelihood estimators for the parameters of the weighted Lindley distribution considering dierent types of censoring, such as, type I, type II and random censoring are presented. A numerical simulation study is performed in order to verify the eciency of our proposed methodology, which is also fully illustrated on two real data set.